Moving in the right direction to fight financial crime: prevention and detection - Fauzi, F.; Szulczyk, Kenneth; Basyith, A. (2018)
© 2018, Emerald Publishing Limited. Purpose: The purpose of this paper is to identify current measures taken for financial crime’s prevention and detection in the context of Indonesia. Design/methodology/approach: This study is based on data from articles in Indonesian newspapers relating to the current financial crimes, current measures of preventing financial crimes in Indonesia and based on the literature review. Findings: There are some attempts to combat financial crimes in Indonesia, both internally and externally. The attempts that have been made for the internal scope are the enactment of anti-money laundering law, the new monitoring system of financial institutions and the formation of a superintendent institution. The attempts that have been made for the external scope are the agreement between Indonesia’ financial intelligence unit Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), and other countries’s financial intelligence unit, the affiliation member of the Asia/Pacific Group on Money Laundering (APG) to combat financial crimes through strengthening its anti-money laundering and terror financing capabilities. Originality/value: This paper presents an overview of current prevention and detection measures in the context of Indonesia, and it is hoped that this paper will contribute to the current discussion of eliminating financial crimes.